2016
DOI: 10.31989/ffhd.v6i8.262
|View full text |Cite
|
Sign up to set email alerts
|

Sauerkraut: A Probiotic Superfood

Abstract: Background: Sauerkraut could potentially be a probiotic superfood. Sauerkraut does not require the use of a starter culture to cultivate these beneficial bacteria. All that is needed is a measure of salt and the cabbage. Naturally made, unprocessed sauerkraut contains probiotic microorganisms called Lactic Acid Bacteria (LAB). LAB is one of the most significant organisms and has established benefits. For example, Lactic Acid Bacteria has established benefits with the treatment of diarrhea, constipation, irrita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Strains of Lactiplantibacillus paraplantarum, L. brevis, and others Lactobacillus strains isolated from sauerkrauts showed adhesion to Caco-2-cells and inhibitory activity towards pathogenic microorganisms [107]. Nielsen et al [112] reported that the effect of sauerkraut consumption on irritable bowel syndrome (IBS) affected a patient and reported that consumption of sauerkrauts, both fresh and pasteurized, led to a reduction of symptoms after 6 weeks, with a change in microbial composition of faecal matters of participants. Also, the high presence of dietary fibers seems to be involved in alleviating IBS symptoms [112].…”
Section: Sauerkrautmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains of Lactiplantibacillus paraplantarum, L. brevis, and others Lactobacillus strains isolated from sauerkrauts showed adhesion to Caco-2-cells and inhibitory activity towards pathogenic microorganisms [107]. Nielsen et al [112] reported that the effect of sauerkraut consumption on irritable bowel syndrome (IBS) affected a patient and reported that consumption of sauerkrauts, both fresh and pasteurized, led to a reduction of symptoms after 6 weeks, with a change in microbial composition of faecal matters of participants. Also, the high presence of dietary fibers seems to be involved in alleviating IBS symptoms [112].…”
Section: Sauerkrautmentioning
confidence: 99%
“…Nielsen et al [112] reported that the effect of sauerkraut consumption on irritable bowel syndrome (IBS) affected a patient and reported that consumption of sauerkrauts, both fresh and pasteurized, led to a reduction of symptoms after 6 weeks, with a change in microbial composition of faecal matters of participants. Also, the high presence of dietary fibers seems to be involved in alleviating IBS symptoms [112]. Cabbages are also rich in phytochemicals with multiple possible bioactivities, but these compounds, mainly glucosinolates, are normally not bioavailable in the fresh product.…”
Section: Sauerkrautmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li et al experimented with the bacteria Bifidobacterium breve in yogurt and found that it showed good stability in vitro and an increased survival rate, even when encapsulated with low methoxyl pectin [12]. Davras et al found that the high probiotic content of kefir enabled modulation of many immunological mechanisms such as regulating IgA, IgG, IL-4, IL-10, and IL-12 levels [20]. On the other end of the spectrum, others have also observed that many probiotic foods failed to survive in high quantity, limiting their effectiveness as functional foods.…”
Section: Probiotic Bacteria In Food Dairy Productsmentioning
confidence: 99%
“…In sauerkraut, 114 isolates of bacteria were discovered, and 85% of those isolates belonged to the Lactobacillus and Leuconostoc genera [15]. Other studies found that despite low initial relative abundance, sauerkraut fermentation resulted in a stable and rapidly established community of lactic acid bacteria that certainly met the recommended CFU range for probiotics [19,20]. In fermented tuna viscera, H. elongata, a bacterium able to remove heavy metals in hypersaline environments and T. halophilus, a lactic acid bacterium, together were capable of the removal of heavy metals, such as Cd, Pb, and Hg, in SNB and MRS broth [21].…”
Section: Non-dairy Productsmentioning
confidence: 99%